RNase L represses hair follicle regeneration through altered innate immune signaling - Kirby, Charles S.; Islam, Nasif; Wier, Eric; Alphonse, Martin P.; Sweren, Evan; Wang, Gaofeng; Liu, Haiyun; Kim, Dongwon; Li, Ang; Lee, Sam S.; Overmiller, Andrew M.; Xue, Yingchao; et al. (The Journal of clinical investigation, 2025)
Mammalian injury responses are predominantly characterized by fibrosis and scarring rather than functional regeneration. This limited regenerative capacity in mammals could reflect a loss of proregeneration programs or active suppression by genes functioning akin to tumor suppressors. To uncover programs governing regeneration in mammals, we screened transcripts in human participants following laser rejuvenation treatment and compared them with mice with enhanced wound-induced hair neogenesis (WIHN), a rare example of mammalian organogenesis. We found that Rnasel-/- mice exhibit an increased regenerative capacity, with elevated WIHN through enhanced IL-36α. Consistent with RNase L's known role to stimulate caspase-1, we found that pharmacologic inhibition of caspases promoted regeneration in an IL-36-dependent manner in multiple epithelial tissues. We identified a negative feedback loop, where RNase L-activated caspase-1 restrains the proregenerative dsRNA-TLR3 signaling cascade through the cleavage of toll-like adaptor protein TRIF. Through integrated single-cell RNA-seq and spatial transcriptomic profiling, we confirmed OAS & IL-36 genes to be highly expressed at the site of wounding and elevated in Rnasel-/- mouse wounds. This work suggests that RNase L functions as a regeneration repressor gene, in a functional trade off that tempers immune hyperactivation during viral infection at the cost of inhibiting regeneration.